# Solve for x and give the fundamental/general solutions: (Sinx - Cosx)^2 = 1^2Show complete solution and explain the answer.

### 1 Answer | Add Yours

You need to expand the binomial `(sin x - cos x)^2` using the formula `(a-b)^2 = a^2 - 2ab + b^2` such that:

`(sin x - cos x)^2 = sin^2 x - 2sin x*cos x + cos^2 x`

You need to remember the basic trigonometric formula `sin^2 x+ cos^2 x = 1` such that:

`(sin x - cos x)^2 = 1- 2sin x*cos x`

You need to substitute `1- 2sin x*cos x` for `(sin x - cos x)^2` in your equation such that:

`1- 2sin x*cos x = 1 =gt -2sin x*cos x = 0 =gt sin x*cos x = 0 (since 2!=0)`

`sin x = 0 =gt x = (-1)^n*sin^(-1) 0 + n*pi =gt x = n*pi`

`cos x = 0 =gt x = +-cos^(-1) 0 + 2n*pi`

`x = +-(pi/2) + 2n*pi`

**Hence, the general solutions to trigonometric equation are `x = n*pi` and `x = +-(pi/2) + 2n*pi.` **